ANALISA FLUKS KALOR KRITIS PADA PERUBAHAN SUHU PELAT DAN LAJU ALIRAN AIR PENDINGIN UNTUK KASUS PEMANASAN-GANDA DI CELAH SEMPIT REKTANGULAR - Kusuma, Muhammad Hadi; Juarsa, Mulya; Antariksawan, Anhar Riza (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
Boiling heat transfer phenomena on rectangular narrow gap was related to the safety of nuclear reactors. Research done in order to study the safety of nuclear reactors in particular relating to boiling heat transfer and useful on the improvement of next-generation reactor designs. The research focused on calculation of the heat flux during the cooling process in rectangular narrow gap size 1.0 mm, with initial temperatures 200 °C, 400 °C, and 600 °C, also the flow rates of cooling water 0,1 liters/second, 0,2 liters/second, and 0,3 liters/second. Experiments carried out by injecting water at a certain flow rate with the water temperature 85 °C. Transient temperature measurement data recorded by the data acquisition system. Transient temperature measurement data is used to calculate the flux of heat gain is then used to obtain the heat transfer coefficient. This research aimed to obtain the correlation between critical heat flux and heat transfer coefficient to changes in temperatures and water flow rates for bilaterally-heated cases on rectangular narrow gap. The results obtained for a constant cooling water flow rate, critical heat flux will increase when hot plate temperature also increased. While on a constant hot plate temperature, coefficient heat transfer will increase when cooling water flow rate also increased. Thus it can be said that the cooling water flow rate and temperature of the hot plate has a significant effect on the critical heat flux and heat transfer coefficient resulted in quenching process of vertical rectangular narrow gap with double-heated cases.